Samotność i osamotnienie u osób w starszym wieku w aspekcie wybranych uwarunkowań - implikacje dla praktyki przeciwdziałania - Sokołowska, Barbara; Szepeluk, Adam (Studia Edukacyjne, 2026)
Nowadays, we are witnessing a demographic phenomenon of continuous ageing of societies, which to varying degrees affects Poland, Europe and other countries around the world. Ageing causes both degradation or limitation of physical fitness and a reduced performance of certain activities; it can be associated with emotional and social losses. Therefore, research was undertaken to identify the causes of loneliness among seniors and their sense of isolation. A survey using a proprietary research tool was conducted among 132 seniors aged 60 to 88, living in Lubelskie Voivodeship. The main research question was To what extent do seniors feel lonely and isolated in the context of certain conditions? The study identified factors that influence the severity of loneliness among the surveyed seniors to varying degrees, and revealed their negative feelings and ways of coping with loneliness. Some of the research outcomes can be successfully used in practice, both in preventive measures and in everyday human functioning.